Il diritto e l’autismo: osservazioni alla legge n. 134/2015 (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The autism spectrum disorder is very complex and varied; for this reason, it can be stated that each autism is different from theother. Legislation therefore, must protect concrete demands as well as constitutional rights, accepting the challenge of its complexity. Consequently, legislators, judges and the public administration play a crucial role, in particular in terms of inclusion in schools. Recent legislative measures have addressed some of the most problematic aspects, however additions and clarifications are required.
Keywords: Autistic Spectrum Disorder; dignity; legal definition; early diagnosis; school inclusion